Spirit of love: a Trinitarian theology of grace - Yong, Amos (Baylor University Press, 2012)
Pentecostal theologian Amos Yong points readers toward an increased theological emphasis on God as love. In Spirit of Love , the first pneumatology of the divine spiritual gift of love, Yong constructs ecumenical and interdisciplinary theology of the Holy Spirit for the church universal. A distinctive contribution toward greater theological reflection on the triune God, Spirit of Love moves readers toward a more complete understanding of God as the source of divine love.